Penyusunan Laporan Keuangan UMKM Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah pada Usaha Kerupuk Spesial Tamban di Sei Lekop Kabupaten Bintan - Marshanda, Marshanda; Andayani, Mery; Syaqilla, Syaqilla; Rikayana, Hadli Lidya (Al-DYAS, 2026)
This study was motivated by the fact that many micro, small, and medium enterprises (MSMEs) have not yet prepared financial statements in accordance with applicable accounting standards due to limited knowledge and resources, as seen in the case of the Kerupuk Spesial Tamban business in Sei Lekop, Bintan Regency, which still uses simple bookkeeping that does not comply with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This study aimed to prepare financial statements for the Kerupuk Spesial Tamban business in accordance with SAK EMKM, identify shortcomings in the existing accounting system, and formulate recommendations to improve the quality of financial reporting in order to support business development. A descriptive qualitative approach was employed, with data collected through interviews, observation, and documentation related to production activities, costs, and financial transactions, which were subsequently analyzed through data reconciliation into the SAK EMKM format, including the statement of financial position, income statement, and notes to the financial statements. The findings show that the application of SAK EMKM produced more systematic, accurate, and informative financial statements, with a positive financial position indicated by assets exceeding liabilities and a significant net profit after adjustments. The preparation of SAK EMKM-based financial statements enhanced transparency and accountability, facilitated operational decision-making, and opened opportunities for access to financing, although full implementation remains constrained by limited human resources. The study concludes that the application of SAK EMKM contributes to improving the quality of financial reporting for MSMEs and recommends consistent daily bookkeeping and the strengthening of business owners’ accounting capacity to ensure business sustainability and growth.